Rancang Bangun Aplikasi Penilaian Kinerja Berdasarkan Sasaran Kerja Pegawai Negeri Sipil Pada Kantor Pertanahan Kabupaten Lamongan - Fransiscus Xaverius Yudha Gamma Christiawan Habel; Henry Bambang Setyawan; Tegar Heru Susilo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Lamongan District Land Office is a regional office of the National Land Agency. Have a role in public service for the people who want to take care the land certificate. Public services do need to have a good quality including the performance of all employees. In Lamongan District Land Office are the so-called performance assessment Job Target Employees. The problem that occurs is a long time calculation and miscalculation performance assessment.Of the problems found then the proposed design the wake application performance assessment based on the target civil servants working in Lamongan District Land Office web based. The application will perform calculations according the formula that has been incorporated in the application, so that it can cope with arithmetic errors that occur and accelerate the calculation time. Applications can be accessed anytime and anywhere, so although officials are outside the assessor's office fixed the performance appraisal can be done.Results of testing with the District Land Office Lamongan is built applications can perform calculations according the formula set forth in SKP. Applications can be accessed through mobile. Applications built to generate employee performance evaluation report by unit and the year requested.Keywords: Land Office, Performance Appraisal, Employee Work Goal